(untitled) (Research, Society and Development, 2021)
Drug-related adverse events can result in socioeconomic repercussions and harm to patients. Thus, the study aimed to evaluate the notifications of medication errors made to the Patient Safety Center of an emergency and emergency hospital in the interior of Bahia. Cross-sectional, descriptive-analytical study carried out in a public emergency and emergency hospital. Data were collected from adverse event notifications made during three months of collection. The type and classification of the error were as determined. The Kolmogorov-Smirnov test was used to assess the normality of the continuous variables, considering p> 0.05 as normal distribution, and to compare the proportions of the categorical variables, Pearson’s chi-square test and Fisher’s exact test were used. 151 notifications of medication errors were identified, classified by type: prescription (51.7%), administration (45.7%) and dispensing (2.6%). These classifications, 12 classifications, being the most frequent: incorrect dose (42.4%), medication omission (26.5%) and administration time (7.9%). The highest occurrence of errors was in the Intensive Care Unit (46.4%). The drug classes most involved with errors were those related to the alimentary tract and metabolism, cardiovascular system and anti-infectives for systemic use. Among the notifying professionals, pharmacists were the ones who performed the most notifications. In view of the identified notifications and considering that medication errors are preventable events, efforts are necessarily made in the search for more information for a better assessment and knowledge of the consequences and possible damages related to medication errors.